2016
DOI: 10.1038/srep22726
|View full text |Cite
|
Sign up to set email alerts
|

Inverse regulation of two classic Hippo pathway target genes in Drosophila by the dimerization hub protein Ctp

Abstract: The LC8 family of small ~8 kD proteins are highly conserved and interact with multiple protein partners in eukaryotic cells. LC8-binding modulates target protein activity, often through induced dimerization via LC8:LC8 homodimers. Although many LC8-interactors have roles in signaling cascades, LC8’s role in developing epithelia is poorly understood. Using the Drosophila wing as a developmental model, we find that the LC8 family member Cut up (Ctp) is primarily required to promote epithelial growth, which corre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 62 publications
0
1
0
Order By: Relevance
“…In addition, a study of the protein interaction network of the mammalian Hippo pathway also revealed interaction between AMOT proteins and LC8 [ 66 ], confirmed by additional large-scale studies [ 67 , 68 ]. A recent work established a connection between LC8 and the Hippo pathway in Drosophila [ 69 ]. In the present work, the LC8 binding sites were experimentally verified both in WWC and the AMOT protein families and were shown to be evolutionarily conserved.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, a study of the protein interaction network of the mammalian Hippo pathway also revealed interaction between AMOT proteins and LC8 [ 66 ], confirmed by additional large-scale studies [ 67 , 68 ]. A recent work established a connection between LC8 and the Hippo pathway in Drosophila [ 69 ]. In the present work, the LC8 binding sites were experimentally verified both in WWC and the AMOT protein families and were shown to be evolutionarily conserved.…”
Section: Discussionmentioning
confidence: 99%